Solid-state electrochromic devices based on poly(trimethylene carbonate) and lithium salts - Barbosa, P. C. (2008)
The application of solid polymer electrolytes as dual-function electrolyte/adhesive components in electrochromic devices and the preliminary characterization of the resulting prototype displays is described in this paper. An asymmetric device configuration, represented schematically as glass/ZnO:Ga2O3/WO3/polymer electrolyte/ZnO:Ga2O3/glass, was chosen. Electrolytes with compositions of n between 3 and 10, where n represents the molar ratio of poly(trimethylene carbonate), p(TMC), ((CO)OCH2CH2CH2O), units per guest lithium ion, were prepared by solvent casting. The electrochromic switching performance was characterized as a function of salt type and salt concentration. The average transmittance in the visible region of the spectrum was above 63% for all the bleached samples characterized. After coloration the structures assembled with both p(TMC)nLiClO4 and p(TMC)nLiBF4 presented an average transmittance in the visible wavelength region above 39%.